Assessment of the body indices and Anguillicola crassus infection status in European eel (Anguilla anguilla) in estuarine systems in Greece - Kantzoura, V; Sapounidis, A; Kouam, MK; Koutrakis, E (Journal of the Hellenic Veterinary Medical Society, 2025)
The European eel (Anguilla anguilla, Linnaeus 1758) is a catadromous, benthic carnivorous predator species that spends most of its life in freshwater, brackish and coastal habitats. Τhe aims of the present study were to examine the morphometric features of European eel population in five estuarine systems in Northern and Western Greece, to investigate the prevalence of Anguillicola crassus and to identify the risk factors associated with an effect to parasitism. The total length of the examined eels (1,343) ranged from 320 mm to 991 mm and the total weight ranged from 46 g to 2,760 g. Condition factor (K) ranged from 0.02 (Mazoma lagoon) to 0.44 (Vistonis and Evros estuarine systems). From the regression results on Lt-Wt relationship, the coefficient of determination (r2) was found to have a strong relationship between Lt-Wt (p<0.01). The overall prevalence of the parasitism was 27.1% (CI: 26.0-31.0). Among the different sampling sites, the eels collected from Vistonis estuarine system had the highest prevalence (63.5%) (CI: 57.8-68.8) following the two lagoons from Mesolonghi lagoon complex: Kleisova lagoon (36.6%) and Tholi lagoon (35.6%). The multivariate binary logistic model analysis demonstrated that the significant factors associated with the infection of A. crassus into the Greek eel population, were the Condition factor K, gender, life stage and eels originate from Vistonis estuarine system. A high level of A. crassus parasitism in various habitats in the study area was located and the nematode is abundant in all A. anguilla habitats in Greece.